The Use of Arm Span and Knee Height for Estimation of Stature among Nepalese Medical Students - Pandey, Niraj; Budathoki, Deepesh; KC, Gopal; Chhetri, Pradeep (Journal of Universal College of Medical Sciences, 2018)
Introduction: Height is a significant parameter for growth and development of an individual. Arm span and knee height measurement are useful when accurate measurement for stature is unobtainable. Studies have shown that the relationship between stature and arm span varies with age and population. Thus, the aim of the present study was to analyze the correlation between stature and two measurements; the arms span and knee height of medical students of Kathmandu Medical College Public Limited, Kathmandu, Nepal. Materials and methods: This is a descriptive study. A total two hundred medical students, presently studying at Kathmandu Medical College, aged between eighteen and twenty eight years were randomly selected as the subjects for the present study. Among them, seventy six were females and one hundred twenty four were males. Arm span and knee height was measured by flexible steel tape and height was taken by stadiometer. The collected data were tabulated and SPSS 20 was used to perform analysis. Results: There is statistically strong correlation (r) between height and arm span (r=0.858, =0.736; r=0.849,=0.720, p<0.01 for males and females respectively) while knee height too has shown a similar relationship (r=0.882, =0.778, r=0.819,=0.670, p<0.01 for males and females respectively). Conclusion: This present study revealed that both arm-span and knee height can be used in estimation of the height of both males and females. The regression equations so derived can be used in cadavers or an amputee or bed ridden patients with fairly accurate results. This can be helpful in medico- legal cases as well as in study of anthropology.